FAKTOR-FAKTOR KEGAGALAN MEDIASI PERKARA CERAI GUGAT TAHUN 2019 DI PENGADILAN AGAMA KELAS 1 A PALEMBANG - Fathanna, Siti Nur; HAK, Nurmala; Sunaryo, Sunaryo (Universitas Islam Negeri Raden Fatah Palembang, 2023)
This research is motivated by the large number of divorce cases being sued in the Class 1 A Palembang Religious Court and the low success rate of mediation, even in 2019 nothing was successful at all. The problems raised in this study are First, what are the factors for the failure of mediation for divorce cases in 2019 at the Class 1 A Religious Court in Palembang. Second, how are the efforts of the Class 1 A Palembang Religious Court to overcome mediation failures for the coming year. The method in this study used the field research research method, which is a type of field research where the data was obtained based on field surveys conducted by collecting information through interviews with mediator judges at the Class 1 A Religious Court in Palembang. The approach used in this study is analytical descriptive, which describes the research object as it is in accordance with the existence and information found. The results of this study are, First, the factors that have resulted in the failure of the mediation of divorce lawsuits in 2019, namely the limited time and energy possessed by the mediator judge, the absence of the parties, the lack of knowledge about mediation, the strong will of the parties which is difficult to reconcile , the interference of a third person, the commotion created during the mediation process. Second, the efforts of the Class 1 A Palembang Religious Court in overcoming mediation failures in divorce cases to be sued for the coming year, namely the Mediator will be changed from a judge to a non-judge who has a mediator certificate, the litigants must attend the mediation process without being represented by attorneys, the mediator must also improve excellent service, mediators must be serious and experienced and can handle the atmosphere during the mediation process. Keywords: Mediation; Divorce; Religious Court